Pesantren as the Basis of Development of Political Ideology in the Digital Era - Rahawarin, Zainal A. (Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2019)
This study aims to investigate the role of Islamic boarding schools as the basis for developing political ideology in the digital era. The research design used is a qualitative approach. The research location is in Ambon, Indonesia. This research was conducted in 2 Islamic boarding schools with 2 pesantren caregivers, and 10 ustadz at the two Islamic boarding schools. Data were collected through observation, interviews, and documentation that focused on three themes, namely the role of Islamic boarding schools, political ideology, and the digital era. The findings in this study reveal that the role of Islamic boarding schools contributes to the strengthening of political ideology in the digital era. The role of the pesantren is carried out through the khalaqoh contained in the pesantren. Khalaqoh is in the form of khalaqoh toriqoh, and also in the form of khalaqoh organization. The perpetrators of the development of political ideology revealed in this study were carried out by the Kyai, as well as the ustadz who was trusted by the Kyai to be badals or substitutes. The development of political ideology through activities in the toriqoh congregation and also the organization's congregation was fairly high. Meanwhile, the weaknesses found in the political ideologicalization by pesantren are not prioritizing the literacy side where the santri and the congregation in the context of ideological politicization tend to be passive. The role of Islamic boarding schools in the digital era continues to contribute to the community to increase their capacity as contributors to the development of political ideology.